Effect of residual pore structure on the performance of TRISO particle fuel - Liu, Shichao; Li, Yuanming; Chen, Ping; Zhou, Yi; Tang, Changbing (Frontiers in Materials, 2023)
The thermal-mechanical performance of tri-isotropic (TRISO) particles with residual pores used in light water reactors (LWRs) was investigated. The effect of residual pore structure on the stress distribution of the inner dense pyrolytic carbon (IPyC) layer, SiC layer, and outer dense pyrolytic carbon (OPyC) layer was studied. The dimensional changes and fission gas release of the fuel particle layers were calculated. Residual pores on the SiC layer can affect the stress distribution of the coated layers. The residual pores, especially the tetrahedrons, may be the source of cracks in the SiC layer, which can break or cause the loss of the capacity of the SiC layer. Residual pores have little influence on the stress distribution of the IPyC and OPyC layers.